New or little known taxa of the plant bug tribe Hallodapini (Hemiptera: Heteroptera: Miridae: Phylinae) from Thailand, with descriptions of three new species of the genus Acrorrhinium Noualhier - Yasunaga, Tomohide; Yamada, Kazutaka; Artchawakom, Taksin (Zootaxa, 2013)
New or little known genera and species of the phyline plant bug tribe Hallodapini are documented. The genus Acrorrhin-ium Noualhier is reported from Thailand for the first time and diagnosed. Three new species, Acrorrhinium kranion, A. lancialium and A. tritonion, are described. The immature forms are confirmed for A. lancialium (5th instar) and A. trito-nion (4th instar); the latter species was found to be associated with Hibiscus tiliaceus L. The little known hallodapines in Asia, Alloeomimus muiri Schuh and Clapmarius thailandana Schuh, are also diagnosed. An annotated check list of the Hallodapini in Thailand and color digital images in life for all currently known Thai species are provided. Hallodapus brunneus (Poppius) is reported from the Oriental Region for the first time.